The development of a permeable pavement from concrete bricks. Issue 1 (March 2021) - Ulfiana, D; Suripin; Budieny, H; Parmantoro, PN; Wibowo, SA
Abstract: Global climate change is causing an increase in the intensity of rainfall in Indonesia. This causes an increased risk of flooding because it is not supported by changes in infrastructure planning and water resource management. Infrastructure construction, especially roads, sidewalks, and parking lots, still uses waterproof construction such as asphalt and concrete. This waterproof construction causes rainwater to not infiltrate to soil layers and consequently rainwater runoff increases. The increasing intensity of rainfall that is not compensated by an increase in infiltration areas causes an increase in the risk of flooding. Therefore, the design of a mixture of concrete bricks that has a high level of permeability needs to be developed to reduce the risk of flooding. This research was conducted by making test samples of four mixture design. The design approach is carried out by varying the proportions between coarse and fine aggregates, and the water-cement ratio. The infiltration testing method was also conducted to accommodate research needs. Based on the analysis, for paving block with an aggregate-cement ratio of 4 by volume, the optimum water-cement ratio was 0.40 with a permeability level of 630 mm/hour and compressive strength of 21.29 MPa.